טעויות בשמש: קריאה בדרמת הטלוויזיה אינדיאני בשמש - חרל"פ, איתי (מכאן, 2017)
In 1981, Israeli television aired Indian in the Sun (Indiani BaShemesh), a television drama directed by Ram Loevy, one of its most prominent directors. Unlike Loevy's Khirbet Hiza'a, which had aired three years earlier and Lehem (Bread), which would air five years later, both of which would later become Loevy's most well-known dramas and enter the canon of Israeli culture, Indian in the Sun was largely forgotten and ignored. However, as this essay illustrates, not only is Indian in the Sun situated chronologically between Khirbet Hiza'a and Lehem, it also shares a thematic focus with both of these important works - the national conflict (Khirbet Hiza'a) and the class and ethnic conflict (Lehem) in particular, and offers a deconstruction and reconstruction of these themes. Thus this essay aims to return to Indian in the Sun and recognize it not only as a rich and complex text, which demands in-depth consideration (and perhaps thereby belatedly grant it canonical status), but also as a groundbreaking work that offers a complex discourse on ethnic, national and gender identities in Israeli society.